Nanodrug delivery systems targeting ferroptosis as an innovative therapeutic approach for Rheumatoid Arthritis - Xiaolin Dai; Yu Zheng; Jianrong Cui; Yuqi Zeng; Bo Yang; Zhanlin Zhang (Materials Today Bio)
Rheumatoid Arthritis (RA) is a chronic inflammatory disease characterized by joint inflammation, progressive cartilage degradation, and bone erosion. Recent research has implicated ferroptosis not only in autoimmune hepatitis but also in the pathogenesis and progression of autoimmune disorders like RA. Consequently, numerous therapeutic strategies have begun to target the ferroptosis pathway, particularly in the design and development of nanodrug delivery systems (NDDSs). While previous reviews have comprehensively discussed the mechanisms of ferroptosis, related signaling pathways, and NDDS materials, recent studies have further elucidated the interplay between ferroptosis and various metabolic pathways, providing a robust theoretical basis for the design of NDDS-based ferroptosis strategies. This review focuses on investigating the role of ferroptosis in the development of RA, aiming to elucidate how targeting ferroptosis can offer novel therapeutic concepts and potential treatments for RA patients. Specifically, it summarizes the design strategies of ferroptosis-based NDDSs via different pathways and highlights the feasibility of RA treatment regimens based on the ferroptosis mechanism. Furthermore, the review critically discusses the current limitations of NDDSs and offers perspectives on future research directions in this field.